High-vertical resolution radiosonde profile of the lower troposphere, Bollebygd, Sweden 2019 - Rayner, David; Wallenberg, Nils; Minola, Lorenzo; Heuzé, Céline (University of Gothenburg, 2019)
Radiosonde profile from a clear day in late winter with rise-rate ~2m/s and 1 second sampling rate.
Key variables: Altitude (m AGL), Pressure (Pascal), Speed (m/s), Heading (degrees), Temperature (C), Relative humidity (%), Latitude, Longitude, Rise speed (m/s).
Wind speed to 3729 m AGL, other variales to 5388 m AGL.

Sonde: Sparv Embedded S1H3-R.

Dataset includes CSV with meteorology and flight history data and kml of flight path.

Radiosonde-profilen från en klar dag på sen vinter med stigningshastighet ~ 2m / s och 1 sekunders samplingsfrekvens.
Hög vertikal upplösning radiosondeprofil av nedre troposfären, Bollebygd, Sverige 2019
Keywords: Atmospheric conditions; Atmosfäriska förhållanden; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Geoscientific Information; Geovetenskap